DEVELOPMENT OF PHYSICAL TEST INSTRUMENTS BASED ON THE CONCEPTUAL KNOWLEDGE DIMENSION OF THE REVISION BLOOM TAXONOMY - Yul Ifda Tanjung; Abu Bakar (Jurnal Pendidikan Fisika, 2019)
This study aims to develop a physics test instrument based on the conceptual knowledge dimension of Revised Bloom's Taxonomy on the topic of General Physics that meets the eligibility criteria of a good test instrument, including validity, reliability, level of difficulty, distinguishing power and effectiveness of fraud. This type of research is a Research and Development (R&D) research with the implementation stages of determining the objectives and indicators of test instruments, compilation of lattices and items, feasibility testing, revision and refinement of test instruments. The data of this study were analyzed qualitatively and quantitatively by trying out the physics test instruments developed in the form of 30 multiple choice tests. Based on the results of qualitative analysis of the content validation aspect, the average rating obtained by the validator is 75.6%, meaning that the test is valid with minor revisions. Judging from the results of the quantitative analysis 20 items were obtained valid with reliability in the very high category, and the level of difficulty in the difficult to easy category, while in the aspect of distinguishing 12 items were in the good category, and 8 questions were in the excellent category and viewed from aspects of deception effectiveness obtained 20 items effective so that it can be concluded, as many as 20 items were accepted and declared worthy to be used to train and measure students' conceptual knowledge on the topic of General Physics